KARBON MESOPORI DARI PIROLISIS POLIMER SINTETIS DAN APLIKASINYA UNTUK PENJERAPAN GAS RUMAH KACA - Achmad Amrizal Fauzi; Imam Prasetyo; Rochmadi Rochmadi; Teguh Ariyanto (Universitas Muhammadiyah Jakarta, 2018)
Pore structures are needed to be tuned depending on utilizations of carbons, hence obtaining high application performances. In this work, mesoporous carbon was synthesized by pyrolysis of polymeric resin of resorcinol-phenol-formaldehyde-ethylene glycol (RPFEG) and employed to adsorb a greenhouse gas of CO2. Carbons were produced at 650-775 oC pyrolysis temperatures. Pore structure was studied by N2-sorption analysis. The results showed that a high quality of carbon results, proven by high specific surface areas and pore volumes in the range of 1000-1300 m2/g and 0,6-1,4 cm3/g, respectively. Mesoporous carbon (>80% mesopores) was obtained when employing pyrolysis temperature of 750 oC. Isotherm curves showed that adsorption at lower temperature is appropriate to obtain a high adsorption capacity. Capillary condensation assisted to obtain high adsorption volume of CO2 up to 30 mmol/g at 25 °C and 30 bar pressure.